The Historical Reality of Abkhazia and the Ethnocentrist Historiography of the Abkhaz: Sokhumi State University - Bakhia-Okrushvili, Salome (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2025)
Historical sources confirm that from the 6th century BCE to the 2nd century CE (until 131 AD), the territory of Colchis and the whole of present-day Abkhazia was inhabited exclusively by Kartvelian (Georgian) populations. In the 2nd to 5th centuries CE, discrete groups of ethnically undefined, nomadic peoples migrated from the North Caucasus to western Georgia. Their language was unknown. By the 7th century, both waves of settlers had easily and naturally assimilated with the more advanced, Christian Kartvelian population. They converted to Christianity and were referred to by Georgians as “Abkhazians,” a name given to these previously unnamed groups. According to sources, in the 16th century, ethnically distinct groups of Jikhs and Abazas, characterized by piratical practices, migrated from the North Caucasus. These semi-nomadic groups raided the native Georgian population, kidnapped people, and killed those who resisted. Young people, women, and children were sold on Ottoman ships across the Black Sea. These settlers appropriated the ethnonym “Abkhaz” from the earlier, 2nd–5th century waves—again, with the help of Georgians. The modern Abkhaz people were formed between the 16th and 18th centuries and have no ethnic or historical connection with the Abkhaz of the 2nd–5th centuries CE. During the Soviet era, contemporary Abkhaz authors began falsifying historical facts. Without reliable sources, they constructed fabricated oral histories and claimed ownership over Georgian ancestral lands.